Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What's the solution of the differential equation $y^4 = k^2 (y^2 + y'^2\csc^2\alpha)$, where $y$ is a function of $x$ and $\alpha$ is a constant?

Polynomial solutions don't seem to work, because the LHS will always have higher degree than the RHS. Solutions of the form $A\cos(x\sin\alpha)+b\sin(x\sin\alpha)$ don't work either, but maybe something similar does?

This comes from the 1st integral of the Euler-Lagrange equation for the functional $\int{y^2 + y'^2\csc^2\alpha)^{1/2}}dx$, which is the arc-length of a curve $r(\theta)$ on a cone with interior angle $2\alpha$, where $y=r$ and $x=\theta$. Perhaps there's a more useful way of using the Euler-Lagrange equation, giving an ODE whose solution is obvious?

share|cite|improve this question
up vote 3 down vote accepted

Here are two possible approaches

1)Solve for $y'^2$: $$y'^2=\frac{y^2(y^2-k^2)}{k^2\csc^2\alpha}=\frac{y^2(y^2-k^2)}{k^2\csc^2\alpha}$$ $$y'=\frac{y\sqrt{y^2-k^2}}{k\csc\alpha}$$ $$dx=k\csc\alpha\frac{dy}{y\sqrt{y^2-k^2}}$$ $$x+C=k\csc\alpha\int\frac{dy}{y\sqrt{y^2-k^2}}$$ Integral on the RHS is evaluated as follows: $$\int\frac{dy}{y\sqrt{y^2-k^2}}=-\int\frac{d\left(\frac{k}{y}\right)}{\sqrt{1-\left(\frac{k}{y}\right)^2}}=\arccos{\frac{k}{y}}$$ Hence, $$y=\frac{k}{\cos{\left(\frac{x+C}{k\csc\alpha}\right)}}$$ 2)Alternatively, confronted with this type of equations involving radicals and even powers of $y$ and $y'$ you might consider looking for a parametric solution introducing trigonometric functions. $$y^{2}+C\sqrt{\left(y^{2}+\frac{1}{\sin^{2}\alpha}y'^{2}\right)}=0$$ Let

$$\sin\alpha\frac{y'}{y}=\tan\psi \qquad (*)$$ $$y^{2}+\frac{Cy}{\cos\psi}=0$$ Ignoring $y=0$ which does not normally satisfy boundary conditions. $$y=-\frac{C}{\cos\psi}$$ Now rewriting $(*)$ as follows $$\sin\alpha\frac{1}{y}\frac{dy}{dx}=\tan\psi$$ solve for $dx$: $$dx=\sin\alpha\frac{dy}{y\tan\psi}=-\sin\alpha\frac{\sin\psi}{\cos\psi\tan\psi}d\psi=-\sin\alpha d\psi$$ Leading to the same result

share|cite|improve this answer
Many thanks for this! – Harry Macpherson Jun 4 '12 at 12:33
(+1) nice answer. – Mhenni Benghorbal Oct 8 '13 at 0:01

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.